2011
DOI: 10.4103/0019-5413.73655
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent idiopathic scoliosis: Indications and efficacy of nonoperative treatment

Abstract: The strategy for the treatment of idiopathic scoliosis depends essentially upon the magnitude and pattern of the deformity, and its potential for progression. Treatment options include observation, bracing and/or surgery. During the past decade, several studies have demonstrated that the natural history of adolescent idiopathic scoliosis can be positively affected by nonoperative treatment, especially bracing. Other forms of conservative treatment, such as chiropractic or osteopathic manipulation, acupuncture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 53 publications
0
30
0
1
Order By: Relevance
“…Although good results can be achieved in patients with JS treated conservatively, there is no known conservative technique able to completely arrest curve progression and to erase the potential need for surgery for this patients population [16][17][18][19][20][21][22]. In particular, Tolo and Gillespie [3] found 27.2 % of their patients treated with the Milwaukee brace needed surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although good results can be achieved in patients with JS treated conservatively, there is no known conservative technique able to completely arrest curve progression and to erase the potential need for surgery for this patients population [16][17][18][19][20][21][22]. In particular, Tolo and Gillespie [3] found 27.2 % of their patients treated with the Milwaukee brace needed surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Coillard et al in 2010 using a SpineCor orthosis reported 37.1 % of patients needed surgery [20]. Other authors have reported higher percentages of patients who needed surgery despite bracing [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients, usually young, have to wear the brace for 18 to 23 hours a day for several years; the brace is often visible and can be uncomfortable to wear. 26 This type of treatment can be rather bothersome 26 and may significantly impact patients' psychological well-being and negatively affect their QoL. 9,21 Bracing may have psychological impacts at the beginning of treatment, including reduced self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Typical nonsurgical treatments include wearing orthotics, stretching and massage, therapeutic exercises, ultrasound or electric stimulation therapy and manual therapy [7][8][9] . Among these methods, therapeutic exercise, strengthening the paraspinal muscles, is recommended as an effective treatment, and is now frequently conducted for the prevention and treatment of scoliosis [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%